Evaluasi penggunaan rekam medis elektronik di rumah sakit: Studi kasus di Rumah Sakit Wahidin Sudiro Husodo Mojokerto - Sheila Aprilia Siswanto; Umi Khoirun Nisak (Poltekkes Kemenkes Aceh, 2024)
Background: Evaluation of the use of medical records is very important. The Mandatory Use of Software Technologies (MMUST) model was created to address this problem focusing exclusively on the environment. Various studies have been conducted with MMUST as a theoretical basis. MMUST has 8 variables which include: system quality, information quality, performance expectancy, social influence, attitude, overall satisfaction, and net benefits.Objectives: This study aims to assess the use of Electronic Medical Records at the Regional General Hospital Wahidin Sudiro Husodo Mojokerto using the Model For Mandatory Use Of Software Technologies and then sharing suggestions or guidelines to increase the use of electronic medical records.Methods: This study used quantitative analytics. The study population was all employees and the study sample was doctors and nurses who were randomly taken in proportion estimation. The sample size is 100. The study was conducted in January 2024 at Wahidin Sudiro Husodo Hospital Mojokerto. Data were collected through questionnaires and in-depth interviews and analyzed using linear regression.Results: The results of the analysis show that Information Quality (IQ) influences Information Satisfaction (IS) (p=0,000). This means that health workers at the DR Regional General Hospital. Wahidin Sudiro Husodo Mojokerto agrees that quality data can be obtained from Electronic Medical Records. But in reality, the use of Electronic Medical Records at the DR Regional General Hospital. Wahidin Sudiro Husodo Mojokerto is still low.Conclusion: Use of Electronic Medical Records in DR General Hospital. Wahidin Sudiro Husodo Mojokerto is still low because respondents stated that many information components have not been accommodated by Electronic Medical Records.